The Effect of Environmental Performance, Green Innovation, and Good Corporate Governance on Financial Performance - Wati, Agustina Sulistyo; Latifah, Lyna (AJAR, 2024)
The aim of this research is to analyze the influence of environmental performance, green innovation, and good corporate governance on financial performance. The population used is manufacturing companies listed on the Indonesia Stock Exchange in 2020 - 2022. This research uses a panel data regression model with a population of 495 units. The number of samples used was 109 units selected using the purposive sampling method. This research uses documentation data collection techniques where data is obtained through financial reports, annual reports and company sustainability reports. The results of this research use panel data regression analysis fixed effect model which shows that partially environmental performance, green innovation and good corporate governance have no effect on financial performance. Meanwhile, environmental performance, green innovation and good corporate governance simultaneously influence financial performance.